Realisation of the Revenue Equalisation Function in Local Government by a General Grants - the Polish Case - Alicja Sekula (Institute of Economic Research (IER), 2017)
Research background: General grants should pursue five different functions. One of them is revenue equalization. This function is achieved if the revenue gap is reduced after the application of the subsidising mechanism. The size of the support should be inversely proportional to own revenues. Purpose of the article: The aim of the article is to analyse the fulfilment of the revenue equalization function by general subsidies. Beside the theoretical analysis, which presents the general grants structure and the functions assigned to them, the article discusses the results of studies showing changes in the revenue gap after the application of the grant mechanism and the correlation between per capita own revenue and the amount of funds from selected parts of the general grant. The following tentative research hypothesis was adopted: general grants fail to fulfil the revenue equalisation function. Methodology/methods: Two research methods were applied: descriptive statistics and correlation - calculating the Pearson correlation coefficient. Findings & Value added: It was concluded that, once the corrective and equalising mechanism was applied, the range between the extreme per capita revenue values was reduced by 40-50% on average, at all local government levels, i.e. at commune, county and province levels, in each year from the period analysed, i.e. 2012-2015. The correlation between the sizes of revenue before and after budget subsidising is always negative, whereas the strength of the relationship ranged between low and significant, depending on the local government level. It was found that general grants do fulfil the revenue equalisation function, which contradicts the initially formulated research hypothesis.
Keywords: H71; H22; H11; 330; general grants; revenue equalization; own revenues; revenue equalisation function; Poland